Notes on species of Empididae (Diptera) described by R. Frey from the Swedish Kamchatka Expedition 1920–1922 - Shamshev, Igor V. (Zootaxa, 2020)
The type material of eight species of Empididae described by R. Frey in his 1935 paper referring to the Swedish Kamchatka Expedition 1920–1922 of René Malaise are revised: E. (Anacrostichus) pachymorion Frey, E. (A.) vicaria Frey, Empis (Polyblepharis) kamtchatica Frey, E. ( Pachymeria) sjoestedti Frey, Hilara galactoptera Frey, H. ragasides Frey, Rhamphomyia (Pararhamphomyia) albibasis Frey; R. (Ctenempis) malaisei Frey. The lectotype is designated for the following species: Empis (Anacrostichus) pachymorion Frey, 1935; E. (A.) vicaria Frey, 1935; Empis (Pachymeria) sjoestedti Frey, 1935; Hilara ragasides Frey, 1935; Rhamphomyia (Pararhamphomyia) albibasis Frey, 1935; Rhamphomyia (Ctenempis) malaisei Frey, 1935. Six valid species are re-described: Empis (Anacrostichus) pachymorion Frey; E. (Polyblepharis) sjoestedti Frey; Hilara lactescens Frey (= H. galactoptera Frey); H. ragasides Frey; Rhamphomyia (Pararhamphomyia) albibasis Frey; R. (Ctenempis) malaisei Frey.